A study on the effects of health behavior and sports participation on female college students' body mass index and healthy promoting lifestyle - Lin, Xiangyun; Liu, Hao (Frontiers in Public Health, 2023)
Modern high-tech and network convenience have changed the lifestyle of modern people. The change of eating habits, the increase of life pressure and the reduction of leisure time lead to the reduction of physical activity time and opportunities, the impairment of physical activity, resulting in insufficient exercise, thus affecting national health. Pender (2002) defined a healthy lifestyle, that is, the spontaneous multi-level perception and behavior of individuals to maintain or improve their health level, as well as self realization and self satisfaction. It can be summed up in six aspects: self realization, health responsibility, nutritional status, interpersonal support, stress management and sports leisure. College is an important and critical period for teenagers to enter adulthood. If we can cultivate a good and healthy lifestyle at this time, we can reduce the risk of chronic diseases in the future. However, at present, there are few studies on the relationship between the healthy promotion lifestyle and body composition of Chinese college students. Therefore, this study adopts a combination of cross-sectional survey and body composition measurement. Its research results will provide useful reference for the design and planning of the physical and mental health curriculum of college students in the future, as well as for improving the level of students' sports activities.